1. Framing Art History. - MINISSALE, GREGORY (Consciousness, Literature & the Arts (1573-2193), 2009)
The author analyzes consciousness in the production and reception of frames in art as well as the language used to describe framing in art history. He describes the essay "Mediations on the Frame," by Jose Ortega y Gasset as an encounter of consciousness and nonconsciousness and imitation of the frame's visual function. He notes that the focus of an article about framing by Jean-Claude Lebensztejn is on the frame in classical art. He examines the notion of transparency in consciousness according to philosopher G. E. Moore.